Environmental drivers and trends in forage fish occupancy of the Northeast US shelf. (2nd November 2021) - Suca, Justin J; Deroba, Jonathan J; Richardson, David E; Ji, Rubao; Llopiz, Joel K
Abstract: The Northeast US shelf ecosystem is undergoing unprecedented changes due to long-term warming trends and shifts in regional hydrography leading to changes in community composition. However, it remains uncertain how shelf occupancy by the region's dominant, offshore small pelagic fishes, also known as forage fishes, has changed throughout the late 20th and early 21st centuries. Here, we use species distribution models to estimate the change in shelf occupancy, mean weighted latitude, and mean weighted depth of six forage fishes on the Northeast US shelf, and whether those trends were linked to coincident hydrographic conditions. Our results suggest that observed shelf occupancy is increasing or unchanging for most species in both spring and fall, linked both to gear shifts and increasing bottom temperature and salinity. Exceptions include decreases to observed shelf occupancy by sand lance and decreases to Atlantic herring's inferred habitat suitability in the fall. Our work shows that changes in shelf occupancy and inferred habitat suitability have varying coherence, indicating complex mechanisms behind observed shelf occupancy for many species. Future work and management can use these results to better isolate the aspects of forage fish life histories that are important for determining their occupancy of the Northeast US shelf.